Me before you [videorecording (DVD)] - Clarke, Emilia, 1986-; Claflin, Sam, 1986-; McTeer, Janet; Moyes, Jojo, 1969- (Warner Home Video, 2016)
Louisa 'Lou' Clark lives in a quaint town in the English countryside. With no clear direction in her life, the quirky and creative 26-year old goes from one job to the next in order to make ends meet. Taking a job at the local 'castle' she becomes caregiver and companion to Will Traynor, a wealthy young banker who became wheelchair bound in an accident. Embarking together on a series of adventures, both Lou and Will get more than they bargained for.